The dynamics of Japanese government bonds' nominal yields - Tanweer Akram; Huiqing Li (Levy Economics Institute of Bard College, 2018)
This paper employs a Keynesian perspective to explain why Japanese government bonds' (JGBs) nominal yields have been low for more than two decades. It deploys several vector error correction (VEC) models to estimate long-term government bond yields. It shows that the low short-term interest rate, induced by the Bank of Japan's (BoJ) accommodative monetary policy, is mainly responsible for keeping long-term JGBs' nominal yields exceptionally low for a protracted period. The results also demonstrate that higher government debt and deficit ratios do not exert upward pressure on JGBs' nominal yields. These findings are relevant to ongoing policy debates in Japan and other advanced countries about government bond yields, fiscal sustainability, fiscal policy, functional finance, monetary policy, and financial stability.
Keywords: E43; E50; E58; E60; G10; G12; 330; Japanese Government Bonds; Long-Term Interest Rate; Nominal Bond Yields; Monetary Policy; Bank of Japan; John Maynard Keynes